2019
DOI: 10.1186/s12284-019-0279-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the first cytokinin glycosyltransferase from rice

Abstract: Background Cytokinins are one of the five major hormones families in plants and are important for their normal growth and environmental adaptability. In plants, cytokinins are mostly present as glycosides in plants, and their glycosylation modifications are catalyzed by family 1 glycosyltransferases. Current research on cytokinin glycosylation has focused on the biochemical identification of enzymes and the analysis of metabolites in Arabidopsis. There are few studies that examine how cytokinin gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Kudo et al (2012) identified three putative cis-ZOGTs in rice, which were shown to preferentially O-glucosylate cZ and cZR rather than tZ and tZR; additionally, cZOGT1 and 2 showed some activity towards tZ, while cZOGT3 was active towards both tZ and tZR. Recently, Li et al (2019) showed a purified Os6 protein Nglucosylated cytokinin in vitro. Heterologous expression in arabidopsis confirmed 7-and 9-NGT activity in planta.…”
Section: Cytokinin Glucosylation Genesmentioning
confidence: 99%
“…Kudo et al (2012) identified three putative cis-ZOGTs in rice, which were shown to preferentially O-glucosylate cZ and cZR rather than tZ and tZR; additionally, cZOGT1 and 2 showed some activity towards tZ, while cZOGT3 was active towards both tZ and tZR. Recently, Li et al (2019) showed a purified Os6 protein Nglucosylated cytokinin in vitro. Heterologous expression in arabidopsis confirmed 7-and 9-NGT activity in planta.…”
Section: Cytokinin Glucosylation Genesmentioning
confidence: 99%
“…cazy.org). Family-1 glycosyltransferases are the largest multigene GT family, and their glycosylated products participate in the regulation of plant growth and development, such as hormone homeostasis 13 , pollination 14 , and interactions with the environment, such as detoxification of xenobiotics 15 as well as UV tolerance 16 . GT1s are also called UDP-glycosyltransferases because they use uridine 5'-diphosphate as a sugar donor.…”
Section: Introductionmentioning
confidence: 99%
“…For protein purification, the GST-tagged protein on the prokaryotic expression vector could be successfully eluted by binding to agarose beads Glutathione Sephrose 4B (purchased from General Electric Company). The specific method was performed in accordance with the work of Li et al (2019), after which the active enzyme was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…For the in vitro enzymatic reaction, the reaction system is shown in Table S1. The specific operation steps were performed in accordance with the work of Li et al (2019).…”
Section: Methodsmentioning
confidence: 99%